2019
DOI: 10.1523/jneurosci.1731-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Subunit α2δ4 Is Regulated by Early Growth Response 1 and Facilitates Epileptogenesis

Abstract: Transient brain insults, including status epilepticus (SE), can trigger a period of epileptogenesis during which functional and structural reorganization of neuronal networks occurs resulting in the onset of focal epileptic seizures. In recent years, mechanisms that regulate the dynamic transcription of individual genes during epileptogenesis and thereby contribute to the development of a hyperexcitable neuronal network have been elucidated. Our own results have shown early growth response 1 (Egr1) to transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 70 publications
(68 reference statements)
2
26
0
Order By: Relevance
“…However, the severity of the phenotype of specific α 2 δ loss-of-function models strongly correlated with the expression level of the particular isoform in the affected cells or tissues: knockdown of α 2 δ-1 affected synapse formation in retinal ganglion cells (Eroglu et al, 2009), lack of α 2 δ-2 causes pre-and postsynaptic defects in hair cells of the inner ear (Fell et al, 2016), knockout of α 2 δ-3 alters presynaptic morphology of auditory nerves (Pirone et al, 2014) and in invertebrates lossof-function of the homologous subunit resulted in abnormal presynaptic development in motoneurons (Caylor et al, 2013;Kurshan et al, 2009), and finally, the predominant expression of α 2 δ-4 in the retina (Knoflach et al, 2013) is mirrored by retinal defects and consequences on the organization of rod and cone photoreceptor synapses (Kerov et al, 2018;Wang et al, 2017;Wycisk et al, 2006). Contrary to these specialized cell types and tissues, the mammalian brain expresses all four known α 2 δ isoforms (Cole et al, 2005;van Loo et al, 2019), whereby the isoforms α 2 δ-1, -2, and -3 are strongly and most ubiquitously expressed (Geisler et al, 2019;Schlick et al, 2010). While the increasing severity of the phenotypes between α 2 δ subunit single and double knockout mice already suggested a functional redundancy, this was ultimately revealed in the cellular triple loss-of-function model established for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the severity of the phenotype of specific α 2 δ loss-of-function models strongly correlated with the expression level of the particular isoform in the affected cells or tissues: knockdown of α 2 δ-1 affected synapse formation in retinal ganglion cells (Eroglu et al, 2009), lack of α 2 δ-2 causes pre-and postsynaptic defects in hair cells of the inner ear (Fell et al, 2016), knockout of α 2 δ-3 alters presynaptic morphology of auditory nerves (Pirone et al, 2014) and in invertebrates lossof-function of the homologous subunit resulted in abnormal presynaptic development in motoneurons (Caylor et al, 2013;Kurshan et al, 2009), and finally, the predominant expression of α 2 δ-4 in the retina (Knoflach et al, 2013) is mirrored by retinal defects and consequences on the organization of rod and cone photoreceptor synapses (Kerov et al, 2018;Wang et al, 2017;Wycisk et al, 2006). Contrary to these specialized cell types and tissues, the mammalian brain expresses all four known α 2 δ isoforms (Cole et al, 2005;van Loo et al, 2019), whereby the isoforms α 2 δ-1, -2, and -3 are strongly and most ubiquitously expressed (Geisler et al, 2019;Schlick et al, 2010). While the increasing severity of the phenotypes between α 2 δ subunit single and double knockout mice already suggested a functional redundancy, this was ultimately revealed in the cellular triple loss-of-function model established for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, we would like to highlight two prominent mutations (Fig. 2, hα 2 δ-4), which affect α 2 δ-4 expression or structure and may, in theory, also affect the previously suggested expression of α 2 δ-4 in the brain [95,117]. A mutation found in night blindness (p.Tyr802Ter) results in a premature stop at amino acid 802.…”
Section: Disease Mutations In α 2 δ Proteinsmentioning
confidence: 87%
“…Until recently, protein and mRNA expression levels of human and murine α 2 δ-4 seemed negligible in all previously examined CNS regions [40,88,95]. A recent study, however, reported increased levels of α 2 δ-4 mRNA in human hippocampal biopsies obtained from epileptic patients, an interesting finding in spite of the lack of information on absolute mRNA levels [117]. Considering that standard curve-based qRT-PCR studies from our group identified very low amounts of α 2 δ-4 mRNA in the mouse brain [40,95], the recent findings suggest the existence of a subpopulation of hippocampal neurons expressing α 2 δ-4.…”
Section: Channel-independent Synaptic Functions Of Potential Relevancmentioning
confidence: 94%
See 1 more Smart Citation
“…2(Bernard et al, 2004;Monaghan et al, 2008), K ir 2 channels(Young et al, 2009), small-conductance (SK) calcium-activated potassium channels(Oliveira et al, 2010), big potassium channels(BK-channels;Pacheco Otalora et al, 2008;Shruti et al, 2008), persistent sodium channels(Agrawal et al, 2003;Chen et al, 2011), the T-type calcium channel Ca V 3.2(Su et al, 2002;Becker et al, 2008) and the calcium channel subunit α2δ4(van Loo et al, 2019).…”
mentioning
confidence: 99%